Aortic cusp extension valvuloplasty: repair with an extracellular patch - Przybylski, Roman; Pawlak, Szymon; Śliwka, Joanna; Urlik, Maciej; Maruszewski, Marcin; Kukulski, Tomasz; Nożyński, Jerzy; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Introduction : The proportion of valve repair procedures is increasing in experienced centers. The aim of the study was to assess the clinical and echocardiographic outcomes after aortic valve reconstruction with a novel surgical technique. Material and methods : The study group consisted of 30 patients (23 male and 7 female) at a mean age of 35 ± 14 years. In patients with aortic root aneurysm the reimplantation or Florida sleeve technique was used. A sub-commissural annuloplasty, plication of the free edge of the cusp, shaving, and commissurotomy were performed. At this stage of surgery aortic repair was then attempted by cusp extension. Since 2013 the strips have been tailored from extracellular matrix. Results: The mean aortic cross-clamp time was 90 ± 32 min. The mean cardiopulmonary bypass time was 126 ± 38 min. There was no in-hospital death. Re-exploration for bleeding was required in 1 patient. During follow-up, 1 patient needed reoperation at 1 year due to endocarditis. All patients remained alive in New York Heart Association (NYHA) functional class I. The echocardiographic findings remained unchanged in all cases during follow-up. Conclusions : Our modification of aortic valve repair results in a good outcome.